Penerapan Model Problem Based Learning Dalam Pembelajaran Menulis Teks Eksposisi Pada Siswa Kelas X - R, Rosyadi; Anggraeni, Neneng (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research is motivated by the low ability of students to develop ideas or thoughts into written language. The aims of this study were 1) to find out the effectiveness of applying the Problem Based Learning model in learning to write exposition texts for class X students of SMK PUI Gegesik in the 2022/2023 academic year; 2) to describe the process of learning to write exposition text by applying the Problem Based Learning model to class X students of SMK PUI Gegesik for the 2022/2023 academic year; and 3) to find out how students respond to learning to write exposition texts by applying the Problem Based Learning model to class X students of SMK PUI Gegesik for the 2022/2023 academic year. The research method used in this research is the experimental method, the type is quasi experimental design. The research design used is nonequivalent control group design. The data in this study are in the form of observational data, tests and questionnaires. Based on statistical results using two independent t tests (Independent Sample t test), a tcount of 2.103 and a ttable of 1.734 are obtained. So tcount> ttable, namely 2.103 > 1.734. This shows that H0 is rejected and H1 is accepted. Thus, it can be stated that the application of the Problem Based Learning model is effective in learning to write exposition texts for class X students of SMK PUI Gegesik in the 2022/2023 academic year. Based on the results of observations made, it is evident that the application of the Problem Based Learning model can increase student activity in learning to write exposition texts. Based on the results of the questionnaire recapitulation as a whole, the average value of students who answered "yes" was 81% and students who answered "no" was 19%, this shows that students respond well to the application of the Problem Based Learning model in learning to write exposition texts in class X SMK PUI Gegesik for the 2022/2023 Academic Year.